The proteinuria selectivity index value predicts the remission of IgA nephropathy: a retrospective cohort study - Ryunosuke Mitsuno; Takashin Nakayama; Wataru Ito; Tomomi Maruki; Ran Nakamichi; Keika Adachi; Norifumi Yoshimoto; Akihito Hishikawa; Aika Hagiwara; Shintaro Yamaguchi; Toshiaki Monkawa; Jun Yoshino; et al. (Renal Failure)
IgA nephropathy (IgAN) is the most common type of primary glomerulonephritis worldwide and leads to end-stage kidney disease. The proteinuria selectivity index (PSI) has been used to assess the prognosis in nephrotic syndrome, but its predictive value in patients with IgAN remains unclear. This single-center retrospective cohort study included patients who diagnosed with IgAN between March 2012 and March 2020. The PSI was calculated at the time of kidney biopsy. Patients were followed up from the time of kidney biopsy to kidney replacement therapy, death, transfer to another facility, or study completion. Ninety-four patients with a median age of 51 years were enrolled and divided according to the cutoff value of PSI determined by the receiver operating characteristic curve analysis into low-PSI (PSI <0.243, n = 39) and high-PSI groups (PSI ≥0.243, n = 55). The median follow-up duration was 70 months. Rates of remission of proteinuria and survival without a two-fold increase in serum creatinine were significantly better in the low-PSI group (both p < 0.01, log-rank test). Cox regression analysis showed that a low PSI was significantly associated with an increased likelihood of remission of proteinuria and hematuria (hazard ratio [HR] 1.96; 95% confidence interval [CI] 1.02–3.85 and HR 1.75; 95% CI 1.01–3.13, respectively), and a decreased risk of a two-fold increase in serum creatinine (HR 0.10; 95% CI 0.01–0.81). In conclusion, The PSI could have the potential to support the assessment of the prognosis of IgAN, in addition to established prognostic markers, by reflecting the overall glomerular permeability.